THE IMPACT OF HALAL CERTIFICATION AND PACKAGING INNOVATION ON IMPROVING THE ECONOMY OF REFILLED WATER MSMES IN LHOKSEUMAWE CITY - Fuadi; Mirna; Mukhlish; Falahuddin; Arliansyah (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The purpose of this study is to examine the influence of awareness, halal certification, packaging innovation, on economic empowerment and the role of halal certification, packaging innovation as a mediating variable between the influence of awareness on economic empowerment in Lhokseumawe City. This research is a quantitative research. The sampling technique uses the sampling census technique (saturation sample) with a total of 37 respondents who are refilling water business in the Lhokseumawe city. The analysis test tool used is SmartPLS 3 with the SEM (Structural Equation Modeling) analysis method. The results of the study stated awareness has no positive and significant effect on halal certification, awareness has no positive and significant effect on packaging innovation, and economic empowerment, halal certification has no positive effect on economic empowerment, packaging innovation has a positive effect on economic empowerment. However, the halal certification variable does not mediate the influence of awareness on economic empowerment and the packaging innovation variable is able to mediate awareness of economic empowerment in refil water business in Lhokseumawe City.